FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA PABRIK TAHU X SEMARANG - Sutrisno, Rizky Andrian; Jayanti, Siswi; Kurniawan, Bina (Jurnal Kesehatan Masyarakat (Undip), 2021)
Personal protective equipment is a set of tools that must be used by workers in the work area as an effort to protect themselves and others from harm. When working, workers of the Semarang X Tofu Factory must use personal protective equipment to avoid work accidents and occupational diseases. The purpose of this study was to analyze the correlation between age, attitude, knowledge, supervision, co-workers, aminities and availability of PPE, with compliance of PPE usage on Tofu X Factory workers in Semarang. Method used in this research is observational analytic with cross-sectional approach. The sampling technique used total sampling with a total of 35 respondents. Instruments used in this research were questionnaire and observation sheet. The results showed that 65.7% of respondents were complied with PPE usage. Based on the chi-square test, it shows that the variables related to compliance of PPE usage were knowledge (p = 0.0) and attitude (p = 0.03). Meanwhile, the variables not related to compliance of PPE use were age (p = 0.918), supervision (p = 0.49), aminities (p = 1.000), co-workers (p = 0.47) and availability of PPE (p = 0, 45). Researcher suggests for the factory to provide PPE according to the workers’ need and establish OSH promotions, for instance safety signs and posters that are placed in accessible areas for workers.